2018
DOI: 10.2217/fca-2017-0074
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed Electrochemical Detection of Three Cardiac Biomarkers cTnI, Ctnt and Bnp Using Nanostructured ZnO-sensing Platform

Abstract: First demonstration of simultaneous detection of three cardiac biomarkers in clinically relevant range with sensor's analytical performance and linear response of detection showed potential utility in screening clinical samples for early diagnosis of acute myocardial infarction and chronic heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…[16][17][18] BNP and cTnI are commonly used cardiac biomarkers. 19 In recent years, it has been found that BNP and cTnI are closely related to myocardial systolic dysfunction. 20 In SS, in addition to the direct action of inflammatory cytokines, the immunopathological response of the complement system and the imbalance of the autonomic nervous system, the dysfunction of mitochondria and abnormal energy metabolism can also lead to myocardial apoptosis and myocardial remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] BNP and cTnI are commonly used cardiac biomarkers. 19 In recent years, it has been found that BNP and cTnI are closely related to myocardial systolic dysfunction. 20 In SS, in addition to the direct action of inflammatory cytokines, the immunopathological response of the complement system and the imbalance of the autonomic nervous system, the dysfunction of mitochondria and abnormal energy metabolism can also lead to myocardial apoptosis and myocardial remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…The EC TN detection method is suitable for those requirements [13,22,27]. The EC TN detection method offers portability (electrode size miniaturized through nano/microtechnology), modularity (can be integrated with a smartphone or arduino-based device), minimal requirements for sample volume, and short measurement time [28,29,30]. Usually, EC TN detection can be achieved by such methods as voltammetric, potentiometric, conductometric, amperometric, and impedimetric techniques [31,32,33].…”
Section: Ec-based Tn Detection System With Nanostructurementioning
confidence: 99%
“…Due to the great importance of the BNP biomarker in CVD diagnosis, analytical immunosensors have been developed for detecting BNP in samples of human serum and whole blood, such as those using transducers based on the field‐effect transistor [9], surface plasmon resonance [10] and photoelectrochemical methods [11]. Given the nanotechnology advances, new emerging technologies constructed on the electrochemical screen‐printed electrode have gained particular attention as an essential analytical tool due to their portability, sensitivity and rapid responses, besides the advantages of large‐scale production with low‐cost [12, 13]. Some approaches based on screen‐printed electrodes have been developed for the BNP [14].…”
Section: Introductionmentioning
confidence: 99%